Challenges in Endobronchial Tuberculosis: From Diagnosis to Management - Surender Kashyap; Anjali Solanki (Pulmonary Medicine)
Despite the rapid advancement in diagnostic and therapeutic modalities, endobronchial tuberculosis (EBTB), defined as tuberculous infection of the tracheobronchial tree, continues to remain challenging for clinicians. Nonspecific respiratory symptoms along with normal chest radiograph in 10–20% of cases may be alleged for the diagnostic delay. Variable diagnostic yield with sputum microscopy might further compound the problem. In such cases, high resolution computed tomography (HRCT) works as a more sensitive tool and demonstrates involvement of tracheobronchial tree described classically as “tree-in-bud” appearance. Bronchoscopic biopsy is considered the most reliable method for confirmation of the diagnosis with 30% to 84% positivity in different series. Evolution of the disease is also unpredictable with frequent progression to bronchostenosis, therefore requiring regular follow-up and early intervention to halt the natural course. This review article elaborates various aspects of the disease with specific focus on diagnostic dilemma and recent advances in interventional bronchoscopy. In addition, this discussion evokes optimism for further research and introduction of innovative therapeutic modalities.